Implementación de una aplicación información app de matemáticas para estudiantes de Básica Superior de la Escuela de Educación Básica Particular Ciudad de Jerusalén - Encalada Escobar, Bernardo Josue; Encalada Escobar, Ernesto Isaac; Gonzaga Franco, Sarai Daiana (Revista Minerva, 2025)
This paper aims to analyze the implementation of a mobile educational application for mathematics learning in 8th, 9th, and 10th-grade students at the Escuela de Educación Básica Particular Ciudad de Jerusalén. The methodology followed three phases: customizing the app with content aligned to the official curriculum, training teachers to integrate the tool into their lessons, and continuous tracking of student progress through the platform’s reports. The results showed that consistent use of the app contributed to improved understanding of complex mathematical concepts, particularly in algebra and geometry. However, some students faced initial challenges in adapting to the technology, highlighting the importance of continuous support. In conclusion, the implementation of this technological tool in the educational process represents an effective strategy to strengthen mathematics learning, though its success depends on ongoing teacher training and proper student support.